Training to improve pro-agility performance: A systematic review - Forster, J. W. D.; Uthoff, A. M.; Rumpf, M. C.; Cronin, J. B. (Journal of Human Kinetics, 2022)
Effective directional change in sport is imperative to success in key game situations. Change of direction (COD) ability is underpinned by various athletic qualities which can be developed through specific and non-specific training methods. This review examined the effect of specific and non-specific training methods on pro-agility performance, by analysing the intervention type and resulting magnitude of training effects on pro-agility shuttle performance. A total of 20 studies were included for review. Data from 638 subjects and 29 intervention groups involving seven different training methods were extracted and analysed in relation to training method classification and primary outcome measures. Interventions involving sprint training, plyometric training, resistance training, and combined resistance, plyometric, and sprint training were found to produce statistically significant positive change on pro-agility performance per session (p < 0.05). Sprint training (0.108 ES), plyometric training (0.092 ES), resistance training (0.087 ES), and combined resistance, plyometric, and sprint training (0.078 ES) methods were found to have the highest per session training effect. While total time is the typical unit of measure for this test, different types of training may lead to preferential improvements in either acceleration, deceleration, or COD phases of the pro-agility shuttle. Specifically, resisted or inclined sprinting may develop the linear acceleration phases, unilateral resistance training may promote increased strength to overcome the imposed forces during the deceleration and COD phases, multiplanar plyometrics can help enhance stretch-shortening cycle capabilities across different force vectors, and a combination of two or more of these methods may enable simultaneous development of each of these qualities.